Relacje między Bogiem a człowiekiem w poezji księdza Jana Twardowskiego - Wasielewska, Magdalena (Dydaktyka Polonistyczna, 2020)
The article concerns the poetry of priest Jan Twardowski. This Catholic priest in his literary works focused on the problem of the relationship between God and man. The poet takes up difficult topics. He does not shy away from showing the issues of suffering, pain and the negative emotions associated with these feelings. Contrary to many religious artists, Twardowski does not show strong tensions in the relationship between God and man. It shows that you can also go through dramatic experiences without losing faith and trust in the Creator. His consistent work not only stands out from the background of Polish religious poetry, but also brings hope and optimism to the readers.